2020
DOI: 10.1016/j.brs.2019.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive current tDCS up to 4 mA

Abstract: Background: Higher tDCS current may putatively enhance efficacy, with tolerability the perceived limiting factor. Objective: We designed and validated electrodes and an adaptive controller to provide tDCS up to 4 mA, while managing tolerability. The adaptive 4 mA controller included incremental ramp up, impedancebased current limits, and a Relax-mode where current is transiently decreased. Relax-mode was automatically activated by self-report VAS-pain score >5 and in some conditions by a Relax-button available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 46 publications
(38 reference statements)
1
40
0
Order By: Relevance
“…This is particularly noteworthy because many of the responders in this study likely would have been classified as non-responders if either of the 'standard' configurations (unilateral) or intensities (2 mA) were used (Figure 2). Fourth, this study adds to the early, but growing, evidence of the tolerability of 4 mA stimulation intensities [29][30][31][52][53][54].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is particularly noteworthy because many of the responders in this study likely would have been classified as non-responders if either of the 'standard' configurations (unilateral) or intensities (2 mA) were used (Figure 2). Fourth, this study adds to the early, but growing, evidence of the tolerability of 4 mA stimulation intensities [29][30][31][52][53][54].…”
Section: Discussionmentioning
confidence: 82%
“…Thus, the effects of higher intensity (4 mA) tDCS on motor function has received little attention [28,29]. Nevertheless, the tolerability of 4 mA tDCS has been shown to be comparable to sham [30,31] or 2 mA [29] and a recent review concluded that there was no evidence that tDCS up to 4 mA for 30 min had any serious negative side effects [27]. Studies exploring the differences in performance between lower (2 mA) and higher (4 mA) intensities are necessary to determine if increasing intensity enhances the desired outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A few limitations are noted for this study. First, although this study recruited more subjects (n = 31) than other tolerability reports ([16] n = 18), it was not as large as other investigations ( [19] n = 50 young, healthy; [1] n = 77 young, healthy; [15] n = 512 young, healthy). Therefore, the relatively small number of subjects in this study may caution generalization.…”
Section: Discussionmentioning
confidence: 93%
“…There are a few that have used intensities >2 mA and have found that 4 mA was safe and well tolerated in stroke survivors [14,16], patients with movement disorders [17], and patients with major depression [18], but each had a very small number of subjects (n < 3). Additionally, a recent report testing an adaptive stimulation controller found that 4 mA tDCS was well tolerated by young adults [19]; however, they did not explore the effects of higher intensity stimulation on a motor task. Thus, investigation of the effects and tolerability of intensities >2 mA is still necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies examining the safety of tDCS for human subjects used careful and moderate stimulation approaches (Bikson et al, 2016 ). However, recent studies have shown that intensities up to 4 mA are safe, tolerable, and do not elicit any serious adverse effects (Bikson et al, 2016 ; Workman et al, 2019 , 2020b ; Khadka et al, 2020 ). Now that the safety and tolerability of tDCS at higher intensities is better established, work exploring the performance differences between moderate (i.e., 2 mA) and higher (i.e., 4 mA) intensities is necessary to determine if increasing intensity further enhances outcomes.…”
Section: Introductionmentioning
confidence: 99%